2021
DOI: 10.1161/jaha.120.018756
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidases 1 and 3 Trigger Atherosclerosis by Desialylating Low‐Density Lipoproteins and Increasing Their Uptake by Macrophages

Abstract: Background Chronic vascular disease atherosclerosis starts with an uptake of atherogenic modified low‐density lipoproteins (LDLs) by resident macrophages, resulting in formation of arterial fatty streaks and eventually atheromatous plaques. Increased plasma sialic acid levels, increased neuraminidase activity, and reduced sialic acid LDL content have been previously associated with atherosclerosis and coronary artery disease in human patients, but the mechanism underlying this association has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 80 publications
1
38
0
Order By: Relevance
“…This suggested that the atheroprotective effects of ASGR1 LOF extended beyond reduction of serum LDLc and could implicate extrahepatic functions of ASGR1, e.g. , in macrophages ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the atheroprotective effects of ASGR1 LOF extended beyond reduction of serum LDLc and could implicate extrahepatic functions of ASGR1, e.g. , in macrophages ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing recognition that native NEU enzymes may play important roles in inflammation and immune cells. (22,30,86,87) We propose that further investigation of the role of these enzymes in B cell regulation is needed. 90) Bacterially-produced enzymes may also be contaminated with LPS, which we observed could alter CD22 clustering.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing recognition that native NEU enzymes may play important roles in inflammation and immune cells. (22,30,86,87) We propose that further investigation of the role of these enzymes in B cell regulation is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that two human ASGR1 -deletion variants found in Iceland, resulting in truncated proteins, likely inactive, are associated with a modest ∼10-14% reduction in LDLc, yet with a significant ∼34% reduced risk of coronary artery disease (12). This suggested that the atheroprotective effects of ASGR1 LOF extended beyond reduction of serum LDLc and could implicate, extrahepatic functions of ASGR1, e.g., in macrophages (36).…”
Section: Discussionmentioning
confidence: 99%